Radec Learning Model With E-Modul: An Effort to Enhance Student Critical Thingking Skills - Anti Muthmainnah; Dede Trie Kurniawan; Rendi Restiana Sukardi; Nur Hidayah Zayadi (PAEDAGOGIA, 2024)
The results of several studies show that the critical thinking abilities of elementary school students in Indonesia are still relatively low. Therefore, this research aims to train elementary school students' critical thinking skills. This research is pre-experimental research using One Group Pretest-Posttest Design. The research instrument used was a pre-test and post-test critical thinking ability test which was processed using the N-Gain formula to measure the influence of the RADEC learning model on students' critical thinking abilities before and after learning activities. The results of the research show that, in terms of critical thinking indicators, the aspects of simple explanation, development of basic skills, concluding, strategy and tactics, have an N-Gain score in the high category, which shows that students' critical thinking skills increase in the high category with an N-Gain score of 0.8 . Meanwhile, for further explanation, it has a value of 0.6 N-Gain in the medium category, which shows that students' critical thinking abilities have increased in the medium category. It can be concluded that the simple explanation aspect is lower than other aspects in students' critical thinking abilities. This shows that students experience a high and moderate increase in critical thinking skills after implementing RADEC-based learning and completing the pre-test and post-test, so that the application of the RADEC-based E-Module is very good for training or improving students' critical thinking skills. critical thinking skills. The E-Module application being developed still needs to be improved in the form of a more attractive presentation and can add more detailed explanations such as commands, tasks, etc.